Clinical study on the impact of microwave ablation energy on the treatment efficacy of benign thyroid nodules - Xue Mei; Xue Mei; Qianqian Fu; Guangyin Li; Xin Ai; Yu Sun; Jiawei Tian; Xiaoping Leng; Shuangquan Jiang (Frontiers in Oncology)
ObjectiveWe aimed to establish a model to estimate the energy required for microwave ablation (MWA) to achieve the desired effect and analyze the factors influencing its therapeutic efficacy.Materials and MethodsWe retrospectively analyzed 117 patients with benign thyroid nodules. A quadratic regression model was established to analyze the relationship between the technical parameters of MWA and volume reduction rate (VRR). Both univariate and multivariate logistic regression analyses were used to identify factors influencing the efficacy of MWA treatment.ResultsThe volume of nodules continued to decrease at 1, 3, 6, and 12 months after ablation, and the mean of VRR was 77.5 ± 15.9% at 12 months after ablation. Among these nodules, 72 (61.5%) had a VRR ≥ 75%, whereas 45 (38.5%) had a VRR < 75%. The energy volume ratio was significantly correlated with the VRR. When the VRR ≥ 75%, the energy volume ratio ranges 784-2,274 J/mL. Among all parameters, only the energy volume ratio and calcification were independent factors influencing the treatment efficacy for benign thyroid nodules (P < 0.05).ConclusionsThe efficacy of the treatment was optimized when the energy volume ratio of the MWA fell within a certain range. The energy volume ratio and calcification are related to the efficacy of MWA treatment.